Digital Supply Chain Integration in Tofu MSMEs of Rambung Merah Village: Integrasi Rantai Pasokan Digital di UMKM Tahu Desa Rambung Merah - Febriana, Vinni; Rahmani, Nur Ahmadi Bi; Silalahi, Purnama Ramadani (Indonesian Journal of Innovation Studies, 2025)
General Background: Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in Indonesia’s economy, particularly in rural areas. Specific Background: Tofu MSMEs in Rambung Merah Village contribute significantly to the local economy but face persistent operational inefficiencies. Knowledge Gap: Despite existing studies on supply chain practices, limited research addresses digital-driven SCM models in rural MSME contexts. Aims: This study aims to analyze the supply chain management (SCM) practices of tofu MSMEs in Rambung Merah Village and identify strategic opportunities to enhance operational efficiency. Results: Findings indicate that while the current SCM involves structured flows from suppliers to end consumers, it remains traditional and constrained by payment delays, logistical issues, and market competition. Novelty: This research introduces a digital integration model into SCM for rural MSMEs, combining qualitative insights with strategic recommendations for technology adoption. Implications: Implementing digital tools—such as e-commerce and social media—supported by digital literacy and logistics training from local authorities, could significantly improve supply chain efficiency, competitiveness, and sustainability of tofu MSMEs in the digital era.Highlight : SCM helps streamline the tofu production and distribution in Rambung Merah. Challenges include late payments, lost equipment, and limited logistics. Digital solutions and training can improve MSME efficiency and competitiveness.   Keywords : Supply Chain Management, MSMEs, Operational Efficiency, Tofu, Rambung Merah